2005
DOI: 10.1136/jnnp.2004.037085
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation: predictors of seizure freedom

Abstract: Objectives: To identify predictive factors for the seizure-free outcome of vagus nerve stimulation (VNS). Methods: All 47 patients who had undergone VNS implantation at one centre and had at least one year of follow up were studied. They underwent complete presurgical evaluation including detailed clinical history, magnetic resonance imaging, and long term video-EEG with ictal and interictal recordings. After implantation, adjustment of stimulation parameters and concomitant antiepileptic drugs were at the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 45 publications
(2 reference statements)
2
82
5
4
Order By: Relevance
“…Four studies additionally included data on the percentage of patients achieving freedom from seizures, typically quoted at the 1-year time frame. 9,15,19,28 Of these studies, seizure freedom was reported at a mean of 14.0% (range 9%-27%). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies additionally included data on the percentage of patients achieving freedom from seizures, typically quoted at the 1-year time frame. 9,15,19,28 Of these studies, seizure freedom was reported at a mean of 14.0% (range 9%-27%). …”
Section: Resultsmentioning
confidence: 99%
“…This volume of information has been used to establish trends in outcome not otherwise evident in investigations with smaller sample sizes. Focal epileptogenic foci and the presence of cortical malformations have been shown to be positive predictors of success with VNS treatment by multiple investigators, including Elliott et al, 10,11 Janszky et al, 19 and Ghaemi et al, 15 but the issue of most appropriate age of implantation appears to remain subject to argument. Ghaemi et al found younger age at initiation of treatment to be a positive predictor, whereas both Elliott et al and Murphy et al found no statistical correlation between younger age and positive outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing application of VNS, it is still not possible to predict which patients respond to what extent to VNS therapy. Most studies that attempt to predict the success of VNS are based upon patient characteristics [4], epilepsy syndrome [5] or localization of the seizure focus [2,6,7]. A meta-analysis by Englot et al on predictors of response to VNS therapy, showed that young patients (<6 years) respond slightly better in terms of seizure reduction compared to adults [2].…”
Section: Introductionmentioning
confidence: 99%
“…A kezdeti klinikai obszervációs vizsgálatok alapján az epilepsziaszindrómák többségében hatékonynak bizonyult [26]. Egy 47 beteg adatainak elemzésén alapuló vizsgálat szerint a jó rohamkimenetel prediktorának a corticalis malformatio és bilateralis EEG-eltérések hiányát találták VNS-implantáció után [27]. Ennek némileg ellentmond az a megfi gyelés, hogy Lennox-Gastaut-szindrómában és az abban jelleg-zetes tónusos axiális rohamokban nagyobb hatékonysá-got mértek [28].…”
Section: Nervusvagus-stimulációunclassified